The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0194599818763137
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Hearing Loss in the Only Hearing Ear: Cochlear Implantation in the Contralateral Deaf Side

Abstract: Objective To investigate the hearing performance of adult patients presenting unilateral deafness with contralateral fluctuating hearing loss who received a cochlear implant on the deaf side. Study Design Case series with chart review. Setting University tertiary referral center. Subjects and Methods Preoperatively and at 6 and 12 months postoperatively, 23 patients underwent pure tone audiometry and speech audiometry with disyllabic and monosyllabic words in a quiet environment and sentences in quiet and nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As stated by Russo et al, 10 "when incapacitating fluctuating hearing loss occurs in patients presenting a contralateral deaf ear, a cochlear implant is indicated in the latter ear, significantly improving performance in noisy conditions and allowing a better quality of communication to be achieved. "…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by Russo et al, 10 "when incapacitating fluctuating hearing loss occurs in patients presenting a contralateral deaf ear, a cochlear implant is indicated in the latter ear, significantly improving performance in noisy conditions and allowing a better quality of communication to be achieved. "…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are few references regarding cochlear implants in patients whose better ears also present some degree of hearing loss. 9,10 This situation can be quite complex, particularly when the hearing in the better ear is apt to progressively deteriorate. The same sort of consideration applies to patients with fluctuant hearing losses in their better ears, as during the episodes of more intense hearing loss, they experiment difficult social and professional situations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was reported that one third of MD cases may have a dysfunction of the immune system (22). Although clinical symptoms of systemic autoimmune disorder were not present in patients who were suspected to have autoimmune pathology-associated MD, studies have identified in these patients an excessive immune response due to an attack of the specific inner ear structures by cochlear innate immune cells that recognize self-antigens, which leads to the release of inflammatory cytokines, including TNF-α, IL-1β, interferonγ (IFN-γ) and IL-17 (23)(24)(25). However, previous studies have shown that autoimmune inner ear disorder is confined mostly to the inner ear (23,24), and whether there is an association between the systemic immune system and local inflammation in the microenvironment of luminal fluid of the ES in patients with MD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence of efficacious medical therapy in the treatment of the MD, despite the many proposed drugs or techniques . Intratympanic therapies with steroid or gentamicin showed some evidence of efficacy; surgical therapy is currently indicated only for cases unresponsive to medical therapy …”
Section: Introductionmentioning
confidence: 99%